Development of the Thai Family Support Scale for Elderly Parents (TFSS-EP) - Komjakraphan, Patcharee; Isalamalai, Sang-arun; Boonyasopun, Umaporn; Schneider, Joanne K. (Pacific Rim International Journal of Nursing Research, 2013)
บทคัดย่อ ครอบครัวเป็นแหล่งสนับสนุนที่สำคัญของบิดามารดาสูงอายุไทย ถึงแม้ว่างานวิจัยนานาชาติ ได้แสดงถึงการประเภทต่างๆ ของการสนับสนุนจากครอบครัว แต่ลักษณะของประเภทต่างๆ ของการสนับสนุนจากครอบครัวไทยยังขาดการศึกษาและความเข้าใจอย่างถ่องแท้ ดังนั้นวัตถุประสงค์ของการวิจัยครั้งนี้ เพี่อสร้างเครื่องมือวัดการได้รับการสนับสนุนจากครอบครัวตามการรับรู้ของบิดามารดา สูงอายุไทย ระเบียบวิธีวิจัยทั้งเชิงคุณภาพและเชิงปริมาณได้นำมาใช้ในการสร้างและพัฒนาเครื่องมือวัดการได้รับการสนับสนุนจากครอบครัวของบิดามารดาสูงอายุไทยข้อคำถามได้มาการทบทวนวรรณกรรมและสัมภาษณ์บิดามารดาสูงอายุไทยจำนวน 35 คนในเนื้อหาที่เกี่ยวกับประเภทและลักษณะของการสนับสนุนที่ได้รับจากบุตร ทดสอบความเที่ยงของเครื่องมือด้วยการวัดซ้ำในบิดามารดาสูงอายุจำนวน 10 คน วิเคราะห์องค์ประกอบในกลุ่มตัวอย่างจำนวน 500 คน เทคนิคการเปรียบเทียบระหว่างกลุ่มถูกนำมาใช้เพื่อเปรียบเทียบความแตกต่างระหว่างค่าคะแนนรวมระหว่างกลุ่มของผู้สูงอายุที่อยู่ร่วมกันกับบุตร (n = 30) และกลุ่มผู้สูงอายุที่อยู่เพียงลำพัง (n =30) ผลพบว่าเครื่องมือวัดการได้รับการสนับสนุนจากครอบครัวมีทั้งสิ้น 61 ข้อ แบ่งเป็น 3 องค์ประกอบ โดยมีค่าความแปรปรวนรวมที่ 57.03% ค่าความเที่ยงมีความคงที่ในการวัดซ้ำ 2 ครั้งในกลุ่มตัวอย่าง 10 คน ในระยะเวลาห่างกัน 2 สัปดาห์ นอกจากนั้นยังพบว่าค่าคะแนนรวมของกลุ่มผู้สูงอายุอยู่ที่อยู่ร่วมกันกับบุตรสูงกว่าค่าคะแนนรวมของกลุ่มผู้สูงอายุที่อยู่เพียงลำพัง กล่าวโดยสรุปเครื่องมือที่สร้างมีคุณภาพและสามารถนำมาใช้วัดการได้รับการสนับสนุนจากครอบครัวไทยของบิดามารดา สูงอายุได้ คำสำคัญ: การสนับสนุนจากครอบครัว การรับรู้การสนับสนุนจากครอบครัวไทย บิดามารดาสูงอายุ Abstract Family is a major resource of support for elderly Thai parents. Although international research has shown several functional aspects of family support, little is known about the functional aspects of family support in the Thai culture. Therefore, the purpose of this study was to develop an instrument for assessing family support for elderly Thai parents. Both quantitative and qualitative approaches were employed in the development and testing of the Thai Family Support Scale for Elderly Parents (TFSS-EP). Items were derived, based on a literature review and interviews with 35 elderly parents, addressing perceptions about types of family support provided by adult children. Factor and item analysis were conducted, with 500 subjects, to determine the structural domains of the instrument. Test-retest reliability of the instrument was determined among 10 elderly parents. Construct validity was determined by comparing differences in the total TFSS-EP’s score between two groups of elderly parents [those living with children (n =30) and those living in a shelter home (n = 30)]. The final instrument contained 61 items that explored family support. Exploratory factor analysis revealed a 3-factor solution, which accounted for 57.03 % of the total variance. Test-retest reliability was stable, between 2 times among 10 respondents over one week, indicating a high degree of stability for all TFSS items. It was noted that elderly parents, who were living with their adult child, had higher scores on the instrument, compared with those living in a shelter home. Thus, the TFSS-EP appears to be a reliable and valid instrument for measuring family support for elderly Thai parents. Key words: family support, perception of family support, elderly Thai parents